Acute spontaneous bilateral rupture of the Achilles tendon: a case report - Plothow, Ana Paula Pereira; Silva, João Luiz Vieira da (Scientific Journal of the Foot & Ankle, 2018)
This is a case report of a 67-year-old active, healthy, male patient who played sports. He presented with pain and bilateral ecchymosis in the calf area. Data from the patient’s history, a physical examination and complementary exams confirmed a diagnosis of atraumatic spontaneous bilateral Achilles tendon rupture. Surgical treatment was performed using the percutaneous technique (the Achillon device) bilaterally. In the postoperative period, the patient used a walking boot with a 3-cm heel lift in maximum equinus for 45 days and in a neutral position until 60 days after the procedure. The patient began rehabilitation with physical therapy and returned to his sporting activities without restrictions. Level of Evidence V; Prognostic Studies; Expert Opinion.